CORPORATE GOVERNANCE - Abdullayeva, Shahzoda Rinat qizi; Xashimova, Salima Nigmatullayevna (Educational Research in Universal Sciences, 2023)
Today, the topic of corporate governance has become vital for the most researches and scientific controversies. The corporate governance is now playing a key role in economic and social development of a country, and it has began to significantly matter for both industrialized and most of the developing countries. In the meantime, little is known for the world community about the state and problems of corporate governance in Uzbekistan.